Is measurement of cervical length an accurate predictive tool in women with a history of preterm delivery who present with threatened preterm labor?. (30th October 2014) - Melamed, N.; Hiersch, L.; Meizner, I.; Bardin, R.; Wiznitzer, A.; Yogev, Y.
ABSTRACT Objective To determine whether sonographically measured cervical length is an effective predictive tool in women with threatened preterm labor and a history of past spontaneous preterm delivery. Methods This was a retrospective cohort study of all women with singleton pregnancies who presented with preterm labor at less than 34 + 0 weeks' gestation and underwent sonographic measurement of cervical length in a tertiary medical center between 2007 and 2012. The accuracy of cervical length in predicting preterm delivery was compared between women with and those without a history of spontaneous preterm delivery. Women with risk factors for preterm delivery other than a history of preterm delivery were excluded from both groups. Results Overall, 1023 women who presented with preterm labor met the study criteria, of whom 136 (13.3%) had a history of preterm delivery (past‐PTD group) and 887 (86.7%) had no risk factors for preterm delivery (low‐risk group). The rate of preterm delivery was significantly higher for women with a history of preterm delivery (36.8% vs 22.5%; P < 0.001). Cervical length was significantly correlated with the examination‐to‐delivery interval in low‐risk women (r = 0.32, P < 0.001) but not in women who had had a previous preterm delivery (r = 0.07, P = 0.4). On multivariable analysis, cervical length was independently associated with the risk of preterm delivery for women in the low‐risk group but not for women with a history of previous preterm delivery. For women with previous preterm delivery who presented with threatened preterm labor, cervical length failed to distinguish between those who did and those who did not deliver prematurely (area under the receiver–operating characteristics curve range, 0.475–0.506). When using standardized thresholds, the sensitivity and specificity of cervical length for the prediction of preterm delivery were significantly lower in women with previous preterm delivery than in women with no risk factors for preterm delivery. Conclusion Cervical length appears to be of limited value in the prediction of preterm delivery among women with threatened preterm labor who are at high risk for preterm delivery owing to a history of spontaneous preterm delivery in a previous pregnancy. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.